Archeologia come esperienza Immagini e immaginari per una conservazione attiva - Palmieri, Alice (Forme del disegno, 2023)
In the book Atmospheres, architect Peter Zumthor begins his reflections on the subject of the sensory perception of a place, observing that "there is a magic of reality, [...] a magic of thought. A passion for beautiful thought". The magic of the real translates into the construction of an experience that simultaneously involves several perceptive stimulations and reaches out to touch and move something deep inside, defining a spatial condition characterised by impalpable and ethereal elements. The book seeks to define the conditions to create an active experience of the archaeological site, through "staging" strategies that consider space as the place of representation in which the transposition occurs, in a certain sense magical, from the plane of reality to its imaginary and conversely. The action on the archaeological site, therefore, is called upon to give structure and form to an idea that acts on the heritage, seeking the ability to dialogue with the context or to redesign it, in order to elaborate a representation that gives life to a narrative. The volume proposes a reflection on the approach to the contemporary use of archaeological heritage, through the reading and analysis of relevant European case studies, in which the definition of visual devices, pathways, covers and forms of reuse makes it possible to perceive and experience what no longer exists, also through the three-dimensional representation of the gap. The images evoked and the resulting imagery belong to a field in which the ability to construct a convincing visual narrative and an effective perceptive dimension is indispensable for a contemporary project of cultural enhancement and promotion.